Características epidemiológicas de los pacientes con intoxicación aguda por organofosforados en el Hospital Isidro Ayora de la ciudad de Loja, 2015. - Rojas Delgado, Carlos David (2016)
Today organophosphate insecticides are pesticides most frequently used worldwide, and therefore are frequent poisonings by these substances, being responsible for almost 80% of pesticide poisoning. This descriptive cross-sectional study was conducted in the Isidro Ayora Hospital in the city of Loja, in 2015, it had as main purpose to determine the epidemiological characteristics of patients with acute organophosphate poisoning. The results obtained indicated superiority of male gender with 66 %, largest age group 20-29 years with 53.19 %, basic instruction with 55.3 % of patients with primary and secondary 40.4 %. The most prevalent occupation was agriculture with 34 %, also higher frequency of patients from rural areas with 68.1 %. The main cause is intentional with 85.1 %. Medical history as 12.8 % of patients had previous poisonings, while 57.4 % had a history of psychiatric illness. It is concluded that the characteristics of the patients involved are male, young, with low education, linked to agriculture, rural origin, intentional poisoning predominant type, with a history of psychiatric illness and poisoning. Keywords: Intoxication, Organophosphates, Cholinesterase.